2005
DOI: 10.1248/bpb.28.560
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Pullulan in Cultured Rat Liver Parenchymal Cells

Abstract: Polysaccharides are an attractive drug carrier directed to the liver because they are distributed in the liver after intravenous injection. Pullulan is a polysaccharide consisting of three a-1,4-linked glucose molecules, polymerized by a-1,6-linkages to the terminal glucose, and has been employed as a carrier of human interferon-b and plasmid DNA to the liver. 1,2) We previously investigated the biodisposition of pullulan in rats and demonstrated that the asialoglycoprotein receptor (ASGPR) contributes to hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…3A, right panel), a carrier we previously synthesized for in vivo neuronal gene delivery [11], was not affected by asialofetuin pretreatment (p ¼ 0.10 and p ¼ 0.50, respectively; t-test). Asialofetuin is best known for competitively binding the asialoglycoprotein receptor (ASGPR), a C-type lectin, and it has indeed been shown that pullulan is internalized into liver parenchymal cells via the ASGPR [13]. In the present study, RT-PCR revealed that DRG sensory neurons do not express the ASGPR-1 and -2 isoforms (Fig.…”
Section: In Vitro Transfection Of Dissociated Dorsal Root Ganglion Nesupporting
confidence: 46%
See 4 more Smart Citations
“…3A, right panel), a carrier we previously synthesized for in vivo neuronal gene delivery [11], was not affected by asialofetuin pretreatment (p ¼ 0.10 and p ¼ 0.50, respectively; t-test). Asialofetuin is best known for competitively binding the asialoglycoprotein receptor (ASGPR), a C-type lectin, and it has indeed been shown that pullulan is internalized into liver parenchymal cells via the ASGPR [13]. In the present study, RT-PCR revealed that DRG sensory neurons do not express the ASGPR-1 and -2 isoforms (Fig.…”
Section: In Vitro Transfection Of Dissociated Dorsal Root Ganglion Nesupporting
confidence: 46%
“…Pitard et al (2004) showed that an amphiphilic poloxamine block copolymer could condense DNA into negatively charged nanospheres for efficient intramuscular gene delivery; however, their particles appeared to enter cells through a liposome-like membrane ''flip-flop'' mechanism that was likely derived from amphiphilicity rather than negative charge [22]. In our experiments, negatively charged but not positively charged pullulan-spermine/DNA appeared to enter cells via a receptormediated mechanism that could be competitively inhibited by asialofetuin, whose archetypal target is the ASGPR receptor [13].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations